Managing Organizational Conflict in the 2019 Concurrent Election In Palembang - Garmien Mellia; Hertanto Hertanto; Arizka Warganegara; Robi Cahyadi Kurniawan (Jurnal Studi Sosial dan Politik, 2021)
In the 2019 concurrent election, the General Election Commission of Palembang City was prosecuted due to the accusation of not executing recommendations and not protecting voting rights. This research aims to : (1) identify the source of internal conflict; (2) identify the source of external conflict, and (3) analyze conflict management applied to resolve the conflict. This research’s method is qualitative descriptive, data were collected through interviews with purposive informants and documentation. Research shows that conflict was mainly caused by lack of regulation and human resources factors which can be specified into internal conflict were caused by personal factors such as (1) communicational barrier; (2) conflict of interest in recruitment; (3) character differences. Functional factors were disproportioned structure and lack of competence. External conflicts were mainly caused by lack of regulation resulted in misperceptions and also personal and intervention factors. By using the framework of organizational conflict management, it has become clear that the General Election Commission of Palembang applied different approaches to conflict management: forcing and withdrawal for ad hoc electoral body, and institutional (legal approach) in dealing with the Election Supervisory Agency of Palembang. Although they might produce some agreements, those types of conflict management were not leading to genuine resolution since it was a win-lose pattern. It is important to formulate rigid regulation, enhance the competence of election organizers, develop check and balance coordination, and synergize as fellow election organizers to avoid conflict reoccurrence in the future.